Misidentification of Streptococcus uberis as a Human Pathogen: A Case Report and Literature Review. (April 2015) - Di Domenico, Enea Gino; Toma, Luigi; Prignano, Grazia; Pelagalli, Lorella; Police, Andrea; Cavallotti, Claudia; Torelli, Riccardo; Sanguinetti, Maurizio; Ensoli, Fabrizio
Highlights: The biochemical phenotyping incorrectly identified E. faecium as S. uberis in humans. We raise doubts about the real occurrence of S. uberis as a human pathogen. S. uberis identification must be supported by genotyping procedures in humans. Summary: Streptococcus uberis is an environmental bacterium responsible for bovine mastitis. It is occasionally described as a human pathogen, though in most cases the identification was based on biochemical phenotyping techniques. This report shows that the biochemical phenotyping may incorrectly identify Enterococcus faecium as S. uberis .